2016
DOI: 10.1007/s00436-016-4950-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of the FLOTAC technique to diagnosing parasites of the urinary tract of dogs

Abstract: Among the nematodes that infect the urinary tract of dogs, the Dioctophyma renale and Capillaria plica are those more frequently reported. For a long time, sedimentation was the only method used to detect eggs of these parasites in urine. The aim of this study was to analyze urine samples (n = 54) of dogs, obtained by bladder catheterization or cystocentesis, by using a modified FLOTAC technique. Animals were divided into two groups, i.e., with (n = 20) and without (n = 34) suspicion of urinary disease. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…However, this present study demonstrates that the FLOTAC technique may be used to diagnose the contamination of lettuces by immature forms of gastrointestinal parasites of animals, and perhaps permit overcoming the limits presented by the classical sedimentation method extensively used. The importance of the FLOTAC technique for the detection of gastrointestinal parasites of animals is indisputable [6,10]; however, the present study opens new possibilities for the use of this technique, beyond its use only in animals.…”
Section: Discussionmentioning
confidence: 91%
“…However, this present study demonstrates that the FLOTAC technique may be used to diagnose the contamination of lettuces by immature forms of gastrointestinal parasites of animals, and perhaps permit overcoming the limits presented by the classical sedimentation method extensively used. The importance of the FLOTAC technique for the detection of gastrointestinal parasites of animals is indisputable [6,10]; however, the present study opens new possibilities for the use of this technique, beyond its use only in animals.…”
Section: Discussionmentioning
confidence: 91%
“…They are considered important diagnostic methods for egg detection of gastrointestinal parasites in dogs (Lima et al, 2015;Cringoli et al, 2010), and those techniques were used for detection of C. plica eggs in dogs in Italy (Maurelli et al, 2014). Lima et al, (2016) indicated that FLOTAC could increase the probability of correct diagnosis of urinary capillariosis in dogs. Mini-FLOTAC has shown better results than the classical sedimentation technique and could be used instead of FLOTAC in laboratories that cannot centrifuge urine (Lima et al, 2016).…”
Section: Diagnosismentioning
confidence: 99%
“…Lima et al, (2016) indicated that FLOTAC could increase the probability of correct diagnosis of urinary capillariosis in dogs. Mini-FLOTAC has shown better results than the classical sedimentation technique and could be used instead of FLOTAC in laboratories that cannot centrifuge urine (Lima et al, 2016).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the parasite is usually located in one of the kidneys, infection can be bilateral, and worms may also develop to adulthood ectopically in sites such as the abdominal cavity, uterus, ovary, mammary gland, urethra, subcutaneous tissues of the inguinal region, and mesenteric lymph nodes [ 1 , 23 ]. Recent studies have implemented a more sensitive technique for detecting and counting Dioctophyme renale eggs in urine [ 24 ]. Nevertheless, this and other currently used diagnostic methods for dioctophymatosis may fail to detect premature, infertile, single sex, or ectopic infections, and the equipment required makes screening for the infection in rural and economically deprived areas difficult.…”
Section: Introductionmentioning
confidence: 99%